Mineral and bone disorder of maintenance hemodialysis patients in Chuzhou - XU Qi; YE Li-ping; CHENG Wei; GAO Lu; SUN Ai-hua; GAO Ye-hu; LIN Li; CHEN Tian-hao; YAO Yin-ping; YAO Yong (Linchuang shenzangbing zazhi)
Objective To understand the mineral and bone disorder(MBD) status of the maintenance hemodialysis(MHD) patients in Chuzhou.Methods The MHD patients were investigated in hemodialysis centers of 7 hospitals in Chuzhou from April 2014 to June 2014.Study data included general demographic characteristics,laboratory examination,clinical manifestation and medications,etc.Taking KDOQI and KDIGO guidelines as standard respectively,success rate of adjusted serum calcium,phosphorus,and intact parathyroid hormone(iPTH) was observed,and then compared with the dialysis outcomes and practice patterns study(DOPPS4).At last,success rate of adjusted serum calcium,phosphorus,and iPTH in patients with MHD was compared in hospitals of various grades.Results(1) Among the selected 1021 cases,598 cases were male and 423 cases female.Mean age in patients was(56.8 ± 17.3) years old and the average dialysis time was(46.6 ± 37.3) months.The top three original diseases were chronic glomerulonephritis(50.1%),diabetic nephropathy(20.2%) and hypertensive nephrosclerosis(14.1%).(2) Based on KDOQI guidelines,the control rate of adjusted serum calcium,serum phosphorus,and iPTH in MHD patients was 40.5%,37.4%and 21.3%,which was lower than that based on DOPPS4(56.7%,52.6%and 29.6%)(all P<0.01).(3) On the basis of KDIGO guidelines,the control rate of adjusted serum calcium,serum phosphorus,and iPTH in MHD patients was 51.5%,19.8%and 46.2%respectively.(4) By comparing hospitals of various grades on the basis of KDOQI guidelines,we found that the control rate of serum phosphorus and iPTH in patients admitted to tertiary hospitals was higher than to secondary hospitals(P<0.05),while the control rate of adjusted serum calcium had no obvious difference.(5) The treatment situation of MBD:On the basis of KDIGO guidelines,the inappropriate treatment of low serum calcium,hyperphosphatemia and secondary hyperparathyroidism accounted for 47.5%,47.6%and 32.5%respectively.Conclusions The control rate of serum calcium,phosphorus and iPTH in MHD patients of Chuzhou is very low.MHD patients in tertiary hospitals have more ideal control situation than secondary hospitals,indicating that close monitoring and management are expected to improve the success rate.